AB0403 Foot Involvement in Rheumatoid Arthritis Patients. (9th June 2015) - Helal, A.-M.H.; El Kaffash, D.M.N.E.; Shahen, E.M.; Hassan, M.M.; Abdel-Fattah, Y.H.
Abstract : Background: Rheumatoid Arthritis (RA) is a chronic inflammatory disorder affecting small and middle-sized joints. Although patients with RA complain of foot pain and foot problems, (1) physicians generally overlook or neglect the feet in rheumatologic evaluation. Part of the problem is a lack of appropriate training in clinical examination techniques. Also outcome measures such as the disease activity score 28 joints (DAS 28), generally used to assess disease activity and remission does not include the feet and ankles. (2) Objectives: The aim of this study was to assess frequency of forefoot as well as hind foot and ankle involvement in RA patients and their correlation with disease activity, disability and bone loss. Methods: Forty three female RA patients 40.17±6.09 years diagnosed according to 2010 ACR/EULAR criteria with a median disease duration of 6.08±5.38 years were included in this study, they consisted of 31 ACPA positive and 12 ACPA negative patients. Forefoot as well as hind foot and ankle involvement were considered when patient complained of pain or swelling and/or tenderness was elicited on examination. Disease activity and disability was scored by DAS 28 and Health Assessment Questionnaire (HAQ) respectively. Bone mineral density (BMD) of the hip and lumbar spine was measured by dual energy X ray absorptiometry (DXA). Results: Forefoot involvement was found in 20 (47%) patients, ACPA positive patients showed a significantly higher percentage of forefoot involvement (0.019). Hind foot and ankle involvement was found in 25 (58%) of patients, ACPA positive and negative patients had similar hind foot and ankle involvement (0.089). There was a statistically significant correlation between bone loss at the hip and forefoot involvement (0.019). There was a statistically significant correlation between ACPA levels and hind foot and ankle involvement (0.047). Conclusions: Forefoot and hind foot involvement is common in RA patients. ACPA positive patients have a higher risk for forefoot involvement. Rheumatoid arthritis patients with forefoot involvement are at a higher risk of bone loss at the hip. The higher the ACPA level the higher the risk of ankle involvement. References: Otter SJ, Lucas K, Springett K, Moore A, Davies K, Cheek L, et al. Foot pain in rheumatoid arthritis prevalence, risk factors and management: an epidemiological study. Clinical rheumatology 2010;29(3):255-71. Borman P, Ayhan F, Tuncay F, Sahin M. Foot problems in a group of patients with rheumatoid arthritis: an unmet need for foot care. The open rheumatology journal 2012;6:290. Acknowledgements: DXA was done in and founded by Alexandria Regional Center for Women's Health and Development. Disclosure of Interest: None declared